Good Policies and Practices on Rural Transport in Africa : Planning Infrastructure and Services - Hine, John (World Bank, Washington, DC, 2015)
This publication forms part of the work of the Sub-Saharan Africa Transport Policy Program (SSATP) on identifying and promoting good policies and practices in rural transport in Africa. It provides an overall framework for identifying, planning, and prioritizing rural transport infrastructure and services interventions. Inadequate rural transport is a major factor contributing to the poverty of the rural population of most developing countries. For large parts of rural Africa, walking and headloading are by far the most important means of transport, most of this effort being undertaken by women. A key element is to encourage a holistic understanding of rural transport. In the context of this paper, the term covers both transport at the village and farm levels, as well as the transport services and infrastructure involved with the movement of people and goods within the village area and between villages, rural markets, and urban areas. First and foremost, though, the role of planning and prioritization is emphasized; a process based on reliable data is introduced, along with the elements of clarity and transparency. The planning process includes clearly identified objectives, relevant data, resources and constraints, and alternative scenarios. The intended audience for this paper comprises of officials, planners, economists, and engineers who are concerned with improving the livelihoods of the rural populations of Africa. Since the majority of external funding goes into initiatives for building rural roads, it is argued that much greater attention needs to be given to the other components of rural transport systems. The methods for planning and prioritization of infrastructure and services are discussed, and suggested further research is articulated. Two appendices providing examples of road planning and district planning procedures are included, along with ten figures interspersed throughout the paper.